Role of ERK1/2 and p38 Protein Kinases in Tumors: Biological Insights and Clinical Implications - Aleksandra Emelyanova; Alexander Modestov; Anton Buzdin; Elena Poddubskaya (Frontiers in Bioscience-Landmark)
Significant advancements have been achieved over recent decades in deciphering the molecular mechanisms driving malignant tumor development. Despite this progress, the precise roles of individual genes, their interactions, and the associated signaling pathways involved in tumor proliferation remain insufficiently characterized. Among these pathways, the mitogen-activated protein kinases (MAPKs) extracellular signal-regulated kinase (ERK)1/2 and p38, which regulate essential cellular functions such as growth, differentiation, and apoptosis, have garnered considerable research attention. Building on recent insights into MAPK signaling, we identified components closely linked to ERK1/2 and p38 activity and examined changes in their behavior during tumorigenesis. Furthermore, we developed quantifiable metrics to assess ERK1/2 and p38 activity, including the ERK/p38 ratio, a key indicator of tumor cell proliferative or quiescent states, along with activation levels of these signaling pathways. Our findings underscore the potential of ERK and p38-related gene expression and pathway dynamics as biomarkers for predicting clinical outcomes and informing tailored therapeutic approaches.